Effect of APOE ε4 genotype on amyloid‐β, glucose metabolism, and gray matter volume in cognitively normal individuals and amnestic mild cognitive impairment. (29th December 2022) - Li, Weihua; Li, Runtian; Yan, Shaozhen; Zhao, Zhilian; Shan, Yi; Qi, Zhigang; Lu, Jie
Abstract: Background and purpose: The presence of apolipoprotein E ε 4 ( APOE ε 4) is associated with an increased risk of developing Alzheimer disease (AD). The aim of this study was to assess the effects of APOE ε 4 on amyloid‐β (Aβ) pathology, glucose metabolism, and gray matter (GM) volume and their longitudinal changes in healthy control (HC) and amnestic mild cognitive impairment (aMCI). Methods: We included 50 HCs and 109 aMCI patients from the Alzheimer's Disease Neuroimaging Initiative phase 2/GO based on availability of baseline T1‐weighted magnetic resonance imaging, 18 F‐florbetapir positron emission tomography (PET), and 18 F‐fluorodeoxyglucose (FDG) PET. Of these, 35 HCs and 67 aMCI patients who underwent 24‐month scans were included for follow‐up study. Results: Voxelwise analysis revealed that APOE ε 4 carriers exhibited greater baseline Aβ deposition than APOE ε 4 noncarriers in both diagnostic groups. However, there was no significant difference between APOE ε 4 noncarriers and APOE ε 4 carriers in terms of 18 F‐FDG PET standardized uptake value ratio and GM volume. Region of interest‐based analysis showed statistically significant greater Aβ deposition in APOE ε 4 carriers than APOE ε 4 noncarriers only in aMCI patients. Furthermore, APOE ε 4 carriers generally exhibited a greater magnitude and spatial extent of longitudinal changes in Aβ deposition than APOE ε 4 noncarriers in both diagnostic groups. Conclusions: Our findings suggest a differential effect of APOE ε 4 on Aβ pathology, glucose metabolism, and GM volume. Studying APOE ε 4‐related brain changes with neuroimaging biomarkers in preclinical AD offers an opportunity to further our understanding of the pathophysiology of AD at an early stage.